Utilization of kinnow peel extract with different wastewaters for cultivation of microalgae for potential biodiesel production. Issue 3 (June 2019) - Amit; Kumar Ghosh, Uttam
Graphical abstract: Highlights: Kinnow peel extract combined with different wastewaters was used as cultivation medium for T. indica . Growth rate, doubling time, biomass productivity and nutrients removal by T. indica were observed. Maximum lipid productivity of 17.52 mg/L/d in KEMS medium was observed. A significant biomass yield of 1.02 g/L was achieved in KEMS. Abstract: High cost of nutrients is a major limiting factor in achieving economically viable microalgal biodiesel production. In this study, three economically feasible cultivation medium containing sufficient amount of organic and inorganic nutrients required for algal biomass production were prepared from the extracts of kinnow peel separately in combination with dairy wastewater, sewage and distilled water. A maximum of 1.02 ± 0.03 g/L biomass yield was achieved with T. indica in KEMS in 24 days of cultivation period. Removal of micronutrients like 66.19% Ca, 27.33% K, 73% Mg, 44.28% Mn, 89.62% Al, 57.14% Fe, 59% Cu and 65.38% Pb were obtained in KEMS medium. T. indica consumed 95, 67% and 70% of ammoniacal nitrogen from KEM, KEMD and KEMS medium, respectively. The FAME profile of T. indica in KEMS contained myristic acid (0.53%), pentadecanoic acids (1.47%) palmitic acid (26%), oleic acid (28%), linoleic acid (18%), linolenic acid (5%) and eicosanoid acid (18.5%) as major fatty acids. Physical properties of biodiesel in KEMS were in an acceptable range of standards EN14214 and ASTM6751, and were also comparable with plant oil methyl esters. This study suggests that kinnow peel extract with different wastewaters produced high biomass and it is economically viable medium for biodiesel feedstock production.